HUMIC ACID CRACKING BY ACTIVATED CLAY CATALYSTS AND IDENTIFICATION OF ITS PRODUCTS - Abdullah, Abdullah; Twinasty, Rina; Rohman, Taufiqur (TROPICAL WETLAND JOURNAL, 2015)
Humic acid is a compound of colloidal, amorphous, and complex aromatic polymer with functional groups of -COOH (carboxyl), -OH (phenol), and C = O (carbonyl). The presence of these functional groups provides a rationale for assuming that humic acids have a potential to produce phenolic, carboxylic and carbonylic compounds through cracking process. In this study the cracking was done by isolating humic acids from peat soil, and facilitated by a clay catalyst which had been activated. Humic acids were isolated by extracting the acids from the peat with NaOH and HCl. The characterization of humic acids included the determination of the ash content by gravimetric method and the analysis of the functional groups of humic acids by Infrared spectrometer (FTIR). The clay to be activated was shaped into two forms, pellets and 20-40 mesh granules. The clay was activated by immersing it in HCl and NH4NO3, and then calcined. The characterization of catalysts included the determination of acidity and the Si/Al ratio gravimetrically, as well as the analysis of the pore volume, maximum pore radius, surface area and average pore radius by Surface Area Analyzer NOVA-1000. Humic acid cracking was performed by a fixed-bed reactor system at a temperature of 400°C. The Liquid smoke, the product of cracking, was analyzed by GC and GC-MS to determine the number of compounds and major compounds contained in the liquid smoke. The results show that the isolated humic acid had ash content of 9.10%. Activated clay had acidity and Si/Al ratio higher than the clay before actifated.  Based on the analyses of GC and GC-MS it can be found out that the major compounds contained in liquid smoke, the product of humic acid cracking with 20-40 mesh catalyst at a temperature of 400°C were phenolic compounds (74.56%), and no carboxylic and carbonylic compounds as the major compounds. The activated clay can be used as the catalyst for humic acid cracking.Keywords: humic acid, catalyst, clay, cracking.